Smart City Service System Design Based On Microservice Architecture: Case Study in Magelang City - Adhi Utomo, Muhammad Tri; Hartanto, Rudy; Sulistyo, Selo (2022)
The micro service-oriented platform provides a flexible and scalable implementation to accommodate the various services offered to citizens in the smart city concept. Integration is a problem that arises along with the widespread application of smart cities, which are seen as a service system. The purpose of the research is to design a good service system as a solution to existing problems. The study will be more specific on service systems as part of implementing smart cities by referring to previous research. Service system engineering is the method, and it takes a top-down, holistic approach. This research results in a microservice architecture design for smart city service system engineering. The resulting design can be a guide to providing decent and better services for citizens. Â© 2022 IEEE.